Development of automated annotation software for human embryo morphokinetics. Issue 3 (12th March 2020) - Feyeux, M; Reignier, A; Mocaer, M; Lammers, J; Meistermann, D; Barrière, P; Paul-Gilloteaux, P; David, L; Fréour, T
Abstract: STUDY QUESTION: Is it possible to develop an automated annotation tool for human embryo development in time-lapse devices based on image analysis? SUMMARY ANSWER: We developed and validated an automated software for the annotation of human embryo morphokinetic parameters, having a good concordance with expert manual annotation on 701 time-lapse videos. WHAT IS KNOWN ALREADY: Morphokinetic parameters obtained with time-lapse devices are increasingly used for the assessment of human embryo quality. However, their annotation is time-consuming and can be slightly operator-dependent, highlighting the need to develop fully automated approaches. STUDY DESIGN, SIZE, DURATION: This monocentric study was conducted on 701 videos originating from 584 couples undergoing IVF with embryo culture in a time-lapse device. The only selection criterion was that the duration of the video must be over 60 h. PARTICIPANTS/MATERIALS, SETTING, METHODS: An automated morphokinetic annotation tool was developed based on gray level coefficient of variation and detection of the thickness of the zona pellucida. The detection of cellular events obtained with the automated tool was compared with those obtained manually by trained experts in clinical settings. MAIN RESULTS AND THE ROLE OF CHANCE: Although some differences were found when embryos were considered individually, we found an overall concordance between automated and manual annotation of human embryo morphokinetics from fertilization to expanded blastocyst stage (r 2  = 0.92). LIMITATIONS, REASONS FOR CAUTION: These results should undergo multicentric external evaluation in order to test the overall performance of the annotation tool. Getting access to the export of 3D videos would enhance the quality of the correlation with the same algorithm and its extension to the 3D regions of interest. A technical limitation of our work lies within the duration of the video. The more embryo stages the video contains, the more information the script has to identify them correctly. WIDER IMPLICATIONS OF THE FINDINGS: Our system paves the way for high-throughput analysis of multicentric morphokinetic databases, providing new insights into the clinical value of morphokinetics as a predictor of embryo quality and implantation. STUDY FUNDING/COMPETING INTEREST(S): This study was partly funded by Finox-Gedeon Richter Forward Grant 2016 and NeXT (ANR-16-IDEX-0007). We have no conflict of interests to declare. TRIAL REGISTRATION NUMBER: N/A